COMMUNICATIVE AND PRAGMATIC WAY OF LEARNING IT TERMINOLOGY - Abdirazzakova , Sadokat Alimbayevna (Educational Research in Universal Sciences, 2023)
This article provide information about communicative and pragmatic ways of effective learning IT (Information Technology) terminology. It contains several strategies that learners need to focus on in obtaining IT terms and useful activities that can be used to teach them in the classroom.